Cylinder sleeve code scanning lubricating device - SHI SHENGXIANG; ZHU WEI; QIAN CHENGZHI; MENG FANXI; TAISHI KEN; XU WEI (2025)
The invention belongs to the technical field of engine manufacturing, and discloses a cylinder sleeve code scanning lubricating device. A limiting sleeve is further rotationally installed on the rotary table, the upper side of the limiting sleeve is sleeved with an air cylinder sleeve, an oiling component is installed on one side of the rotary table and comprises a first support and an oil outlet valve, the oil outlet valve is connected with a lubricating oil supply component, and an outlet of the oil outlet valve abuts against the outer wall of the air cylinder sleeve on the limiting sleeve. A code scanning component is further installed on one side of the rotary table and comprises a second support and a camera, the camera is installed on the second support, a two-dimensional code is displayed on the outer wall of the air cylinder sleeve, and the camera recognizes the two-dimensional code; the problems that in the prior art, code scanning and lubricating processes need to be completed on different stations,